Perancangan Perangkat Pengendali Navigasi AR Drone Quadcopter Berbasis Hand Gesture dengan Metode Complementary Filter - Syarif Hidayatullah; Gembong Edhi Setyawan; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Quadcopter is a type of Unmanned Aerial Vehicle (UAV) which widely used in various fields of life. Navigation control is a very important thing to know while using quadcopter. Navigation control is a way to set the direction of quadcopter movement when flying. Remote control can be used to control the direction of quadcopter. But, using the remote control is required specific ability for the user to set the direction of quadcopter movement. Natural User Interface (NUI) is a new way to interact with a system. NUI made human easier to interact with the system. Because NUI using natural input such as the movement of the human body. In this research built a wearable device which can detect hand gesture and control the movement of quadcopter. The device applies complementary filter method to reduce noise when detecting angle transformation when user doing hand gesture. Based on the tests that had been done, this system got succes on each test of hand gesture. Delay in this system generates when the user doing hand gesture until the quadcopter move is 0.67 seconds.